Adapting scenarios for climate adaptation: Practitioners' perspectives on a popular planning method. Issue 104 (February 2020) - Butler, James R.A.; Bergseng, Anne Marte; Bohensky, Erin; Pedde, Simona; Aitkenhead, Matt; Hamden, Rohan
Highlights: Scenario planning for climate adaptation is increasingly popular but has not been evaluated. We present reflections from practitioners at the European Climate Change Adaptation conference. Participatory processes focussed locally over short (<20 year) timeframes were most effective. Scenario planning did not sufficiently engage in decision-making processes, limiting outcomes. Reflexive 'transient scenarios' embedded in iterative adaptation pathways were recommended. Abstract: Scenario planning is a popular decision-support method that is increasingly being applied to climate change adaptation. However, evaluation of scenario planning for adaptation is lacking. In this paper we summarise a science-policy session held at the European Climate Change Adaptation Conference in May 2019, where practitioners explored the strengths and weaknesses of scenario planning for climate adaptation and identified modifications to enhance the method's utility. Eight case studies spanning three scenario planning types (problem-focused, actor-focused and reflexive-interventionist) from varied socio-cultural contexts were presented by the authors, followed by discussion amongst the 40 participants. Strengths focussed on opportunities provided by scenario planning for stakeholder participation, and raising their awareness about future risks, vulnerability and uncertainty. Participatory scenario planning was most useful for building stakeholder consensus at the local scale (e.g. communities, neighbourhoods) over shorter timeframes (e.g. 20 years). Weaknesses centred on the inability of scenarios to generate quantitative predictions and concrete adaptation solutions. This was partly attributed to practitioners' limited understanding of stakeholder politics and power dynamics, and the resulting lack of integration of scenario exercises within decision-making processes. Scenarios were also limited by being static, and participatory processes were resource-intensive. Suggested modifications were to develop iterative scenario planning embedded within decision-making cycles. Such 'transient scenarios' could absorb system feedbacks and updated information to prioritise adaptation responses, thus actively contributing to ongoing adaptation pathways. Applying monitoring, evaluating and learning would enable reflexive refinement of the method, adapting it to become an agile approach applicable to varied socio-cultural and political contexts.